Lgr4 regulates mammary gland development and stem cell activity through the pluripotency transcription factor Sox2. (4th October 2013) - Wang, Ying; Dong, Jie; Li, Dali; Lai, Li; Siwko, Stefan; Li, Yi; Liu, Mingyao
ABSTRACT: The key signaling networks regulating mammary stem cells are poorly defined. The leucine‐rich repeat containing G protein‐coupled receptor (Lgr) family has been implicated in intestinal, gastric, and epidermal stem cell functions. We investigated whether Lgr4 functions in mammary gland development and mammary stem cells. We found that Lgr4 −/− mice had delayed ductal development, fewer terminal end buds, and decreased side‐branching. Crucially, the mammary stem cell repopulation capacity was severely impaired. Mammospheres from Lgr4 −/− mice showed decreased Wnt signaling. Wnt3a treatment prevented the adverse effects of Lgr4 loss on organoid formation. Chromatin immunoprecipitation analysis indicated that Sox2 expression was controlled by the Lgr4/Wnt/β‐catenin/Lef1 pathway. Importantly, Sox2 overexpression restored the in vivo mammary regeneration potential of Lgr4 −/− mammary stem cells. Therefore, Lgr4 activates Sox2 to regulate mammary development and stem cell functions via Wnt/β‐catenin/Lef1. Stem Cells 2013;31:1921‐1931